2011
DOI: 10.2165/11539640-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Tobacco Control Policies in Vietnam

Abstract: All four interventions to reduce the harm from tobacco use appear to be highly cost effective and should be considered as priorities in the context of Vietnam. The government may initially consider graphic warning labels and tax increase, followed by other interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…To curb the use of tobacco products, tobacco taxation remains the most cost-effective anti-smoking intervention [28, 29]; however, strong political opposition has remained a major barrier to wider implementation. In addition to increasing taxes on tobacco, other strategies that may be successful in reducing tobacco use include public advertisements, legislation to ban smoking in public places [30, 31], and pictorial warnings on tobacco products, which has been successful in both high-income and middle-income countries [32, 33]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…To curb the use of tobacco products, tobacco taxation remains the most cost-effective anti-smoking intervention [28, 29]; however, strong political opposition has remained a major barrier to wider implementation. In addition to increasing taxes on tobacco, other strategies that may be successful in reducing tobacco use include public advertisements, legislation to ban smoking in public places [30, 31], and pictorial warnings on tobacco products, which has been successful in both high-income and middle-income countries [32, 33]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…39 Studies reviewing the cost-effectiveness of other tobacco control policies have reported that tobacco control interventions generally, including public smoking bans, are highly cost-effective. 40,41 Many US campuses have implemented less than full smoke-free policies. Studies of 25-foot buffers near building entrances have shown this to be ineffective at reducing SHS exposure.…”
Section: Principal Findingsmentioning
confidence: 99%
“…For example, we simulated the effects of higher mortality among smokers (and former smokers) on future smoking prevalence, which the SimSmoke model does not. In addition, using national data linkage studies from New Zealand,25 26 we could model the mortality risks by age, sex, level of smoking and ethnicity for the New Zealand population and project these risks forward in time based on historic ethnic-specific trends; rather than relying on the American Cancer Society’s Cancer Prevention Study II from the 1980s to define relative risks of mortality among current and former smokers (as in previous modelling for Australia18 and Vietnam27). …”
Section: Discussionmentioning
confidence: 99%